Peculiarities of Disinfection of Microbiological Safety Cabinets and Premises of Virological Laboratories when Carrying out Works with the Smallpox Virus - V. V. Zolin; O. P. Os’kina; M. N. Eremina; G. F. Davydov; T. A. Gosteva (Проблемы особо опасных инфекций, 2020)
Objective. Applying microbiological method to determine the effectiveness of disinfection treatments with formaldehyde fumigation of the hidden cavities and the reverse side of the microbiological safety cabinet filters (MSC) located in the “infectious” areas of an isolated to maximum extent laboratory. Evaluation of the effectiveness of experimental unit for automation of the formaldehyde treatment of laboratory premises. Materials and methods. Assessment of effectiveness of disinfection treatments of MSCs and the premises of virological laboratory was carried out using cambric test objects contaminated with the spore-forming test culture of B. thuringiensis. Results and discussion. The disinfection time sufficient for the complete inactivation of particularly dangerous pathogenic microorganisms potentially located in hidden cavities and on the back side of microbiological safety cabinet filters, placed in the “infectious” zone of the most isolated laboratory has been determined experimentally. As a result of the studies, it was possible to achieve complete inactivation of the spore-forming test microorganism located on test objects situated in hidden cavities and hardly accessible places of MSC at concentration of 1·106 cells/cm3 only with disinfection time equal to 24 hours. Effective disinfection of test objects contaminated with B. thuringiensis spore-forming test culture, placed in hard-toreach places and on the back of the equipment in a boxed virological room, using an experimental plant producing gaseous formaldehyde, was possible only when formalin was used in a concentration of 40 ml/m3 of the room. It was established that the amount of formalin required to achieve 100% efficiency of the disinfection treatment of the virological boxed room using an experimental unit producing gaseous formaldehyde depends on the operating mode of the general supply and exhaust ventilation, the configuration of the laboratory room, and the furnishing with laboratory and engineering equipment.